Investigating the Effect of PV Panel Mounting Orientation under Partial Shading Conditions (A Simulation-Based Study) - Usman, Usman; Achmad , Alamsyah; Sofyan , Sofyan; Sirad, Mochammad Apriyadi Hadi; Hidayatullah, Syarif; Isman, Muh (INTEK: Jurnal Penelitian, 2025)
This study aims to investigate the effect of shading on the mounting orientation of PV panel and the availability or unavailability of Bypass Diodes on the performance of PV panel under partially shading conditions. In this study, for each PV panel mounting orientation, the number of PV cells that received shading was grouped into three categories: 9 cells, 18 cells and 27 cells respectively with the shading fixed vertically. The study also considers the availability and unavailability of bypass diodes. The simulation results show that with vertical shading partially covering the PV cells, the landscape mounting orientation is the best orientation for PV panels with bypass diodes to avoid the partial shading effect